Antihypertensive and Vascular Benefits of Blueberries in Postmenopausal Women - Hoyle, Brian (MD Conference Express, 2014)
Hypertension (HTN) is a modifiable risk factor for cardiovascular disease, and the causes are multifactorial but are partly due to endothelial dysfunction, which results in decreased vasodilation and increased vasoconstriction. This article discusses the addition of blueberries to diets in order to arterial stiffness and decrease blood pressure.